The Clinical Impact of Imaging Surveillance and Clinic Visit Frequency after Acute Aortic Dissection - Chaddha, Ashish; Eagle, Kim A.; Patel, Himanshu J.; Deeb, G. Michael; Yang, Bo; Harris, Kevin M.; Braverman, Alan C.; Hutchison, Stuart; Evangelista, Arturo; Fattori, Rossella; Froehlich, James B.; Nienaber, Christoph A.; Isselbacher, Eric M.; Montgomery, Dan G.; Kline-Rogers, Eva; Woznicki, Elise; LaBounty, Troy M. (AORTA, 2019)
Background Guidelines recommend frequent follow-up after acute aortic dissection (AAD), but optimal rates of follow-up are not clear.Methods We examined rates of imaging and clinic visits in 267 individuals surviving AAD during recommended intervals (≤1, > 1–3, > 3–6, > 6–12 months, then annually), frequency of adverse imaging findings, and the relationship between follow-up and mortality.Results Type A and B AAD were noted in 46 and 54% of patients, respectively. Mean follow-up was 54.7 ± 13.3 months, with 52 deaths. Adverse imaging findings peaked at 6 to 12 months (5.6%), but rarely resulted in an intervention (3.4% peak at 6–12 months). Compared with those with less frequent imaging, patients with imaging for 33 to 66% of intervals (p = 0.22) or ≥66% of intervals (p = 0.77) had similar adjusted survival. In comparison to patients with fewer clinic visits, those with visits in 33 to 66% of intervals experienced lower adjusted mortality (hazards ratio: 0.47, 95% confidence interval: 0.23–0.97, p = 0.04), with no difference seen in those with ≥66% (vs. < 33%) interval visits (p = 0.47). Imaging at 6 to 12 months (vs. none) was associated with decreased adjusted mortality (hazards ratio: 0.50, 95% confidence interval: 0.27–0.91, p = 0.02), while imaging during other intervals, or clinic visits during any specific intervals, was not associated with a difference in mortality (p > 0.05 for each).Conclusions Adverse imaging findings following AAD are common, but rarely require prompt intervention. Patients with the lowest and highest rates of clinic visits experienced increased mortality. While the overall rate of surveillance imaging did not correlate with mortality, adverse imaging findings and related interventions peaked at 6 to 12 months after AAD, and imaging during this time was associated with improved survival.
Keywords: aortic diseases; aorta; diagnostic imaging